Perbandingan Penilaian dalam Kurikulun 2013 dengan Kurikulum Merdeka - Ahmad Dailami Taunie; Hindun Hindun (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
The 2013 curriculum focuses on developing students' knowledge, understanding, abilities, values, attitudes and interests, with the aim of enabling them to apply this knowledge in a practical way. At the same time, it encourages independent learning based on each student's abilities, while providing opportunities for the development of character and important skills. This research uses a qualitative descriptive approach using a literature study review. This research aims to determine the differences between the 2013 Curriculum and the Merdeka Curriculum in various aspects, including characteristics, objectives, competencies, assessment methods and roles. The findings of this research can help the government choose a more effective curriculum for students, thereby optimizing the learning process for their future. Based on the research we conducted, we have drawn conclusions and provided recommendations to the government, emphasizing the need for well-developed policies, thorough outreach, and comprehensive teacher training before implementing curriculum changes. In the end, it is the teacher who will be directly involved with students in the learning process.